Magnesium acetyltaurate prevents retinal damage and visual impairment in rats through suppression of NMDA-induced upregulation of NF-κB, p53 and AP-1 (c-Jun/c-Fos) - Lidawani Lambuk (Neural Regeneration Research, 2021)
Magnesium acetyltaurate (MgAT) has been shown to have a protective effect against N-methyl-D-aspartate (NMDA)-induced retinal cell apoptosis. The current study investigated the involvement of nuclear factor kappa-B (NF-κB), p53 and AP-1 family members (c-Jun/c-Fos) in neuroprotection by MgAT against NMDA-induced retinal damage. In this study, Sprague-Dawley rats were randomized to undergo intravitreal injection of vehicle, NMDA or MgAT as pre-treatment to NMDA. Seven days after injections, retinal ganglion cells survival was detected using retrograde labelling with fluorogold and BRN3A immunostaining. Functional outcome of retinal damage was assessed using electroretinography, and the mechanisms underlying antiapoptotic effect of MgAT were investigated through assessment of retinal gene expression of NF-κB, p53 and AP-1 family members (c-Jun/c-Fos) using reverse transcription-polymerase chain reaction. Retinal phospho-NF-κB, phospho-p53 and AP-1 levels were evaluated using western blot assay. Rat visual functions were evaluated using visual object recognition tests. Both retrograde labelling and BRN3A immunostaining revealed a significant increase in the number of retinal ganglion cells in rats receiving intravitreal injection of MgAT compared with the rats receiving intravitreal injection of NMDA. Electroretinography indicated that pre-treatment with MgAT partially preserved the functional activity of NMDA-exposed retinas. MgAT abolished NMDA-induced increase of retinal phospho-NF-κB, phospho-p53 and AP-1 expression and suppressed NMDA-induced transcriptional activity of NF-κB, p53 and AP-1 family members (c-Jun/c-Fos). Visual object recognition tests showed that MgAT reduced difficulties in recognizing the visual cues (i.e. objects with different shapes) after NMDA exposure, suggesting that visual functions of rats were relatively preserved by pre-treatment with MgAT. In conclusion, pre-treatment with MgAT prevents NMDA induced retinal injury by inhibiting NMDA-induced neuronal apoptosis via downregulation of transcriptional activity of NF-κB, p53 and AP-1-mediated c-Jun/c-Fos. The experiments were approved by the Animal Ethics Committee of Universiti Teknologi MARA (UiTM), Malaysia, UiTM CARE No 118/2015 on December 4, 2015 and UiTM CARE No 220/7/2017 on December 8, 2017 and Ethics Committee of Belgorod State National Research University, Russia, No 02/20 on January 10, 2020.